A pan-European model of landscape potential to support natural pest control services. (July 2018) - Rega, Carlo; Bartual, Agustín M.; Bocci, Gionata; Sutter, Louis; Albrecht, Matthias; Moonen, Anna-Camilla; Jeanneret, Philippe; van der Werf, Wopke; Pfister, Sonja C.; Holland, John M.; Paracchini, Maria Luisa
Abstract: Pest control by natural enemies (natural pest control) is an important regulating ecosystem service with significant implications for the sustainability of agro-ecosystems. The presence of semi-natural habitats and landscape heterogeneity are key determinants of the delivery of this service. However, to date, synthetic and consistent indicators at large scales are lacking. We developed a pan-European, spatially-explicit model to map and assess the landscape potential to sustain natural pest control. The model considers landscape composition in terms of semi-natural habitats types, abundance, spatial configuration and distance from the focal field. It combines recent high-resolution geospatial layers with empirical results from extensive field surveys measuring the specific contribution of different semi-natural habitats to support insects flying enemies providing natural pest control. The resulting maps facilitate a comparison of the relative biological control potential of different areas and show that currently a large proportion of high-productive agricultural areas in Europe has low potential. The obtained indicator can inform the formulation of policies and planning strategies aimed at increasing biodiversity and ecosystem services and can be used to assess trade-offs between different services. Potential fields of application include the Common Agricultural Policy and the EU Biodiversity Strategy, in particular the implementation of Green Infrastructure.